Innate immune response to human mesenchymal stem cell implantation in immunocompromised mice - Xia, Z; Taylor, P; Gordon, S; Cui, Z; Triffitt, J (2004)
The innate immune system in response to human mesenchymal stem cell (hMSC) implantation in immunocompromised mice and the possible mechanism of hMSC was investigated. Spleen and blood samples from normal and hMSC implanted CB17 scid beige were collected for FACS analysis of myeloid markers. Immunohistochemistry of myeloid cell markers in spleen were found to be consistent with FACS analysis. The results demonstrates that the CB17 scid beige mice were activated in normal and inflammatory condition.